Pengaruh Tipe Industri dan Gender Diversity terhadap Pengungkapan Emisi Karbon - Karunia Zuraidaning Tyas; Anastasia Anggarkusuma Arofah; Nugroho Budi Wirawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to provide evidence of how industry type and board gender diversity influence carbon emissions disclosures made in manufacturing companies listed on the Indonesia Stock Exchange for the period 2020 to 2022. The sampling in this study used a purposive sampling technique. Based on these criteria, 81 observations were obtained. Research findings show that the type of industry influences carbon emissions disclosure, gender diversity influences carbon emissions disclosure. It is hoped that the findings of this research can contribute to expanding the disclosure of carbon emissions by companies, especially Indonesia, thereby helping the Indonesian government to more easily control the country's carbon emissions.